Naproxen Sodium Release from Poly(acrylic acid-co- N-vinyl-2-pyrrolidone) Hydrogels - D. Radhy, Nadher (Al-Qadisiyah Journal of Pure Science, 2018)
Copolymer hydrogels of acrylic acid (AA) and N-vinyl-2-pyrrolidone (NVP), crosslinked with 1,4-butanediol dimethacrylate (BDDMA), were prepared by radical copolymerization. The chemical structures of copolymer hydrogels were analyzed by Fourier transform infrared spectrometer (FTIR) and H NMR spectroscopy. The swelling ratio (Rs) was measured for four types of hydrogels structures, in three different media pH 1.2 , 4 and 7.4 at 370C as a function of time. A Naproxen Sodium is used as a model drug to investigate the drug release profile of the hydrogels. The concentration of drug released was measured on UV-Vis spectrophotometer. Results indicated that the swelling ratio and drug release is increase concentration decrease of crosslinked agent and pH increase.